The role of the acetabular labrum in hip dysplasia: A literature overview - Hartig-Andreasen, Charlotte (Informa Healthcare, 2013)
A periacetabular osteotomy (PAO) is the preferred joint preserving treatment for young adults with symptomatic hip dysplasia and no osteoarthritis. In symptomatic dysplasia of the hip, there is labral pathology in up to 90% of cases. However, no consensus exists as to whether a labral tear should be treated before the periacetabular osteotomy (PAO), treated simultaneously with the PAO, or left alone and only treated if symptoms persist after the PAO. This review is an update of aspects of labral anatomy and function, the etiology of labral tears in hip dysplasia, and diagnostic assessment of labral tears, and we discuss treatment strategies for coexisting labral tears and hip dysplasia.